Aspects of the educational context in the Amazonian boundaries: the case of the Brasiléia-Epitaciolândia conurbation - Silva, Leonardo Luiz Silveira da (Geografares, 2017)
This article focuses on the spatial analysis of educational data collected in the cities of Brasiléia and Epitaciolândia. Such cities had specific characteristics as its position near the border with Bolivia and their twin city status shared with Cobija, capital of the Bolivian department of Pando. Such specificities express their educational situation investigated. The article will present and discuss the existence of relations between conurbated urban centers, the movement of people in search of educational facilities and the geographical profile of the students in this still little studied region of Brazilian territory. Such presentation will be through the data collected in field research and complemented by educational IBGE data basis. Keywords: National Border; Twin Cities; Education.